The Impact of the Special Autonomy Fund on Indigenous Papuans (OAP) and Support for the TNI-Polri - Prasetyo, Soya Ani; Widodo, Pujo; Sutanto, Rudy (Formosa Journal of Science and Technology, 2024)
Special Autonomy (Otsus) for Papua is a central government policy that aims to improve the welfare of indigenous Papuans (OAP) through infrastructure, education, health, and economic development, as well as supporting TNI-Polri operations in maintaining security in the region. Despite the large amount of special autonomy funds allocated, reaching IDR 8.5 trillion by 2022, major challenges remain in achieving equitable prosperity for indigenous Papuans. The Human Development Index (HDI) in Papua increased slightly to 60.62 in 2021, but remains the lowest nationally. In addition, only about 8% of indigenous Papuans are categorized as prosperous. This study aims to analyze the impact of the use of special autonomy funds on the welfare and quality of life of indigenous Papuans, evaluate the role of these funds in supporting TNI-Polri operations, and assess the effectiveness of their allocation in supporting local government activities and maintaining security stability in Papua. The results show that despite improvements in the welfare of the Papuan people and support for the operations of the TNI-Polri, the unequal distribution and use of funds remains a challenge. Therefore, increased transparency, accountability and public participation in the management of Special Autonomy funds are necessary to ensure equitable and sustainable benefits for all Papuans.